PENGEMBANGAN GAME EDUKASI BERBASIS ANDROID PADA MATERI ANGKA MATEMATIKA DI PAUDQU DARUNNAJWA KOTA CILEGON: PENGEMBANGAN GAME EDUKASI BERBASIS ANDROID PADA MATERI ANGKA MATEMATIKA DI PAUDQU DARUNNAJWA KOTA CILEGON - Chandra Dewa (Cakrawala Pedagogik, 2025)
Chandra Dewa, 2024. Development of an Android-Based Educational Game for Learning Numbers and Mathematics at Darunnajwa Early Childhood Education (PAUDQU) in Cilegon City. Smart Apps Creator 3 is a learning medium frequently used by teachers and students in the learning process. Using less engaging learning media can easily make students bored and less able to understand the material presented, especially in learning numbers and mathematics. The researcher's goal was to develop a valid, practical, and effective Smart Apps Creator 3 medium for use in learning numbers and mathematics at Darunnajwa Early Childhood Education (PAUDQU) in Cilegon City. The type of research used was research and development (R&D). R&D is the activity of developing or creating a product for use in the learning process. The ADDIE model used in this study consists of five stages: analysis, design, development, implementation, and evaluation. The Smart Apps Creator 3 learning media was validated by experts in terms of content, design, and language, meeting the criteria for validity and practicality. Effectiveness was assessed using questionnaires and student tests. The results showed that the Smart Apps Creator 3 learning media for learning mathematics met the criteria for very valid with a score of 90%, based on design, content, and language validation. The results for practicality were 95%, categorized as very practical. Meanwhile, 94% was categorized as very effective. Therefore, Smart Apps Creator 3 met the criteria for validity, practicality, and effectiveness.